التّكامل الوظيفي بين المدرسة والأسرة في عملية التّنشئة الاجتماعية - درقيش, سميرة; دردوري, صباح (جامعة الوادي university of Eloued, 2016)
Abstract: A study entitled "The functional integration between family and school in the socialization" The school and family issues from the topics of great interest, As well as socialization, which is directed to the main roles. The study aims to find out the functional integration between the school and the family in the process of socialization, And falls within this question a number of sub-questions are as follows: - Does the school function in the socialization process of the pupil. - Does the family function in the socialization process of the pupil. - Is there a consensus among both the school and the family in the socialization process of the pupil. This study aims to: - Identification of functional integration between the school and the family in the process of socialization. A total of 110 pupil through fifth grade from 2 primary school in municipality of El-Oued (Kina El-Aich2, Echahid Debbar Mohammed) Depending on the method of social survey, It was used descriptive method in order to describe the characteristics phenomenon studied and access to the results, For research tool used is the form interviewer to complete the study, and the study concluded the following results: - The school function of socialization of the individual (student) with a rate of 69.2%, education and learning is the basic functions of primary schools. The teacher in primarily mission is to educate students and their education in accordance with the principles enshrined in the community. - The function of the family socialization of the individual (student) with a rate of 66.2%, the family is seeking to trained Semitism relations in a manner adapted to check his social acceptance. - There is consensus among the functions of the school and the family in the socialization process of the individual (student) increased by 67.6%, Integration lies in cooperation and communication and the achievement of social and upbringing of their functions in accordance with the principles are consistent with community standards.
دراسة ميدانية على تلاميذ سنة الخامسة ابتدائي بمدرستي كينة العايش 02 والشهيد دبار محمد بالوادي
مذكرة ماستر في علم الاجتماع تخصص علم اجتماع التربية
Keywords: سوسيولوجيا المدرسة، التنشئة الاجتماعية، سوسيولوجيا الاسرة; Sociologie scolaire, socialisation, sociologie familiale; School sociology, socialization, family sociology